O‘ZBЕK TILIDА TOBЕDOSHLIK АLOQАSI - SH.Mаhsutаliyеvа, SH. (FILOLOGIYA UFQLARI JURNALI, 2022)
In this article, on the materials o the Uzbek language, the speech features of subordination are studied through lexical and syntactic units.